Stability and Performance Evaluation of Advanced Bread Wheat (Triticum aestivum L.) Genotypes in Low to Mid Altitude Areas of Ethiopia - Delesa, Abebe; Dabi, Alemu; Alemu, Gadisa; Geleta, Negash; Solomon, Tafesse; Zegeye, Habtemariam; Duga, Rut; Asnake, Dawit; Asefa, Bayisa; Tadesse, Zerihun; et al. (International Journal of Bio-resource and Stress Management, 2023)
Twenty three advanced bread wheat genotypes have been evaluated against two released bread wheat varieties in 2018−19 and 2019−20 in nine diverse environments of Ethiopia. The experiment was laid out using alpha lattice design with three replications. Ten stability models were employed in order to assess stability and performance of 23 advanced bread wheat genotypes. Combined analysis of variance for grain yield has revealed that the environments, the genotypes and GEI effects were significantly different (p<0.001). In the present study, Environments, GEI and Genotypic effects accounted for 88.6%, 8.3% and 3.1% of the total grain yield variation, respectively. Twelve bread wheat genotypes, ETBW 9136, ETBW 9139, ETBW 9065, ETBW 9080, ETBW 9172, ETBW 9396, ETBW 9452, ETBW 9641, ETBW 9642, ETBW 9646, ETBW 9647 and ETBW 9648 produced grain yield that raged from 5.4 to 5.8 t ha-1, indicating their superior yielding potential. ETBW 9136, ETBW 9139, ETBW 9172, ETBW 9396, ETBW 9452, ETBW 9641, ETBW 9642 and ETBW 9646 were the most stable bread wheat genotypes as confirmed by five to ten stability models. However, ETBW 9452, ETBW 9641, ETBW 9642, ETBW 9646, ETBW 9647 and ETBW 9648 were susceptible to either stem rust or yellow rust or both. Providentially, ETBW 9136, ETBW 9139, ETBW 9172 and ETBW 9396 were superior yielding, stable, resistant and moderately resistant to wheat rusts. Thus, these four genotypes were the most promising advanced bread wheat genotypes to be verified and released in low to mid altitude areas of Ethiopia.